2009 Sixth IEEE International Conference on Advanced Video and Signal Based Surveillance 2009
DOI: 10.1109/avss.2009.90
|View full text |Cite
|
Sign up to set email alerts
|

Landmark Localisation in 3D Face Data

Abstract: Accurate landmark localisation is an essential precursor to many 3D face processing algorithms but, as yet, there is a lack of convincing solutions that work well over a wide range of head poses.In this thesis, an investigation to localise facial landmarks from 3D images is presented, without using any assumption concerning facial pose. In particular, this research devises new surface descriptors, which are derived from either unstructured face data, or a radial basis function (RBF) model of the facial surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 80 publications
(163 reference statements)
0
24
0
1
Order By: Relevance
“…The second variant of descriptors are derived from an implicit radial basis function (RBF) model, they are referred to as surface RBF signature (SRS) features, which are related to the previous work in sampling an RBF model [1]. Both variants of descriptors are a natural extension of the previous work in landmark localisation [1]- [5]. The point-triplet descriptors are able to encode surface information within a triangular region defined by a point-triplet into a surface signature, which could be useful not only for 3D face processing but, also, within a number of graph based retrieval applications.…”
Section: Point-triplet Feature Descriptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The second variant of descriptors are derived from an implicit radial basis function (RBF) model, they are referred to as surface RBF signature (SRS) features, which are related to the previous work in sampling an RBF model [1]. Both variants of descriptors are a natural extension of the previous work in landmark localisation [1]- [5]. The point-triplet descriptors are able to encode surface information within a triangular region defined by a point-triplet into a surface signature, which could be useful not only for 3D face processing but, also, within a number of graph based retrieval applications.…”
Section: Point-triplet Feature Descriptorsmentioning
confidence: 99%
“…Then, using contextual support [2], a pair of candidate landmarks is created. As long as SSR value features robustly detect the pronasale landmark, it was found that many candidate pairs of endocanthions can be deleted, as no pronasale landmarks support them [5]. After this, only candidate landmarks with the minimum Mahalanobis distance to the mean of training SSR value features, within a radius of 10 mm, are kept.…”
Section: Point-triplet Feature Descriptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…(We appreciate that this is a slightly easier problem than using the full scan of head and shoulders, and we will address these larger scans in future work.) The landmarks used are a mixture of contributions from [22] and [19].…”
Section: Databasementioning
confidence: 99%